دور البحث الالكتروني في زيادة التحصيل الدراسي لدى عينة من التلاميذ المتمدرسين بثانوية ميموني عبد القادر بالاغواط - نسرين بن حميد; ديدة فاطمة الزهراء لحرش; بدرية نوعي (My University, 2023)
The current study aimed to find out the role of electronic research in increasing academic achievement among a sample of students attending Maimouni Abdel Qader High School - the first year of secondary school as a model -. The study relied on the descriptive approach, and the two students applied the questionnaire "The role of electronic research in increasing the academic achievement of the schoolchild" prepared by them. The questionnaire was built by reviewing some studies similar to the subject of the study, and the questionnaire was applied to a sample consisting of (41) male and female students distributed over the divisions of arts and experimental sciences. After confirming the validity and stability of the questionnaire, the following results were reached: - Electronic research affects the increase in academic achievement. - There are statistically significant differences in the attitudes of the study sample members on the level of impact of electronic research on academic achievement attributed to the gender variable. - There are statistically significant differences in the attitudes of the study sample members on the level of impact of electronic research on academic achievement due to the specialization variable. Keywords : E-Research, Academic Achievement